Pencapaian Target Standar Pelayanan Minimal (SPM): Apa Yang Terjadi? - Suryanto Suryanto (Jurnal Transformasi Administrasi, 2014)
Enthusiasm of the various parties to the implementation of the policy of minimum service standards turned out to be different. Ministry of the Home Affair (MoHA) , as the leading sector of the successful policy of SPM, is certainly a very active part in voicing that the policy should be run smoothly as mandated by legislation. But beyond that, many other parties actually give a different response, ministries / agencies, for example, assume that a SPM's problem is MoHA's domain so that ministries/agencies does not have to "bother" to pay attention in the implementation of SPM in the area. Meanwhile, local governments both provincial and district / city - especially district / city, assume that the implementation of SPM with outcomes predetermined considered a burden to the budget so it does not need to be supported to the maximum, except for the preparation of standard operating procedures ( SOP ) and standards public services ( SPP ), two terminologies that is often interpreted as an SPM . The debate arises because of ignorance about the definition of the concept of the SPM itself. If so, how can the government expect the achievement of the target.